AN ANALYSIS OF THE NATIONAL CHARACTER BUILDING OFSONGSLYRICS: STAND OUT FIT IN, A MILIONS DREAMS AND BY MY SIDE - Wibowo , Joko; Arifin, Zainul (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
In the era of globalization and modernization, every nation has the opportunity to become an advanced and independent nation, but if the nation does not have strong character and resilience, modernization and globalization will bring threats to the nation. Both